Matemática e saúde: boa alimentação e as equações dos índices IMC, RIP e IAC contextualizadas em situações de sala de aula - Balan, Luanda Helena Balúgoli (2013)
Most students have great difficulty in applying the theory learned in mathematics throughout their academic life. Since the initial series until the final grades of high school, the study of equations, inequations and functions are privileged, with demonstrations of formulas and properties and applications of exercise lists. However, the results of educational assessments at state and national level show that one of the major found student´s difficulties is using the mathematical tools learned throughout their lives, with the aim of resolving everyday problems. Contextualizing the teaching is a way of making significant all the mathematical knowledge and a way of contextualizing is to apply didactic sequences that bring everyday problem situations to the student´s present. The contextualized didatic sequences are strategies that encourage learning in an efficient and meaningful way.